Use of pain management in childbirth among migrant women in Iceland: A population-based cohort study - Gudmundsdottir, E.Y.; Nieuwenhuijze, M.; Einarsdottir, K.; Halfdansdottir, B.; Gottfredsdottir, H. (Birth, 2022)
Background Immigration is rapidly increasing in Iceland with 13.6% of the population holding foreign citizenship in 2020. Earlier findings identified inequities in childbirth care for some women in Iceland. To gain insight into the quality of intrapartum midwifery care, migrant women's use of pain management methods during birth in Iceland was explored. Methods A population-based cohort study including all women with a singleton birth in Iceland between 2007 and 2018, in total 48 173 births. Logistic regression analyses with odds ratios (ORs) and 95% confidence intervals (CIs) were used to investigate the relationship between migrant backgrounds defined as holding foreign citizenship and the use of pain management during birth. The main outcome measures were use of nonpharmacological and pharmacological pain management methods. Results Data from 6097 migrant women were included. Migrant women had higher adjusted OR (aORs) for no use of pain management (aOR = 1.23 95% CI [1.12, 1.34]), when compared to Icelandic women. Migrant women also had lower aORs for the use of acupuncture (0.73 [0.64, 0.83]), transcutaneous electrical nerve stimulation (TENS) (0.92 [0.01, 0.67]), shower/bath (0.73 [0.66, 0.82]), aromatherapy (0.59 [0.44, 0.78]), and nitrous oxide inhalation (0.89 [0.83, 0.96]). Human Development Index (HDI) scores of countries of citizenship <0.900 were associated with lower aORs for the use of various pain management methods. Conclusions Our results suggest that being a migrant in Iceland is an important factor that limits the use of nonpharmacological pain management, especially for migrant women with citizenship from countries with HDI score <0.900.